Determinación de la influencia de la agrobiodiversidad de solanáceas (incluidos dos tubérculos andinos) y el paisaje agrícola en la presencia de punta morada de la papa y del psílido de la papa (Bactericera cockerelli) en los años 2018 – 2019 en las provincias de Cotopaxi, Tungurahua y Chimborazo mediante el empleo de bases de datos existentes e imágenes satelitales. - Naranjo Silva, Joselyn Esmeralda (2022)
Potato purple top and potato psyllid (Bactericera cockerelli) is a phytosanitary problem that has occurred in potato, tomato, tamarillo, bell pepper, cape gooseberry, and other species belonging to the Solanaceae family. However, the relationship between the agrobiodiversity of cultivated solanaceous crops, the components of the agricultural landscape with the presence of PMP, and the potato psyllid are still unknown. The landscape is an environment that, depending on its characteristics, can favor or limit the attack of pests and diseases. The main objective of this research study was to determine the influence of cultivated Solanaceae agrobiodiversity (including two Andean tubers) and agricultural landscape on the presence of PMP and potato psyllid in 2018-2019 in the provinces of Cotopaxi, Tungurahua, and Chimborazo. For this purpose, the database of PMP and potato psyllid monitoring for the years 2018-2019 provided by the Agency for Regulation and Phytosanitary and Zoosanitary Control (Agrocalidad) was used, taking the variables of province, latitude, longitude, altitude, diagnosis and presence, databases from 2012 to 2019 of the Continuous Agricultural Surface and Production Survey (CASPS) considering the variables: INEC code of each parish, province, canton, parish, code of each crop and total area in hectares of each crop per parish, which allowed updating the database generated by Marcalla (2020) on the agrobiodiversity of Solanaceae crops in Ecuador. Landsat 8 level 1 satellite images were also used to obtain data on the agricultural landscape (percentage of bare soil, percentage of crop, and percentage of moorland) surrounding the PMP and potato psyllid monitoring points. The results obtained show that in Ecuador there is an average range of agrobiodiversity of solanaceous crops (including two Andean tubers) from 11.11% to 66.67%. The parishes with the highest average percentage of solanaceous agrobiodiversity are those found in the central-northern sector of the Sierra region. The satellite images used, their temporality and the type of processing used did not allow for obtaining the expected quality data on the composition of the agricultural landscape; however, we worked with the variable altitude, obtained from the database provided by Agrocalidad. The average percentage of Solanaceae agrobiodiversity has a directly proportional influence on the probability of potato psyllid presence and PMP. Altitude has an inversely proportional influence on potato psyllid presence. The increase in altitude produces an increase in the effect of the average percentage of agrobiodiversity of solanaceous crops on the probability of the presence of the potato psyllid. On the other hand, the increase in altitude produces a decrease in the effect of the average percentage of agrobiodiversity of solanaceous crops on the probability of PMP presence.